Phytochemical, analgesic, in-vitro anti-oxidant and GC-MS analysis of Vernonia amygdalina leaves (2018)
The powdered leaf of Vernonia amygdalina was subjected to phytochemical screening, and in vitro antioxidant studies. The volatile oil of the leaves of the plant was also screened to determine the constituents. Analgesic tests using acetic acid induced writhing and paw licking (formalin) test in mice were also carried out. The in vitro antioxidant assay used include FRAP, ABTS, DPPH, and NO assay and then compared these with standards (Vitamin E and Rutin). Results showed the presence of saponins and tannins strongly, while alkaloids, flavonoids, anthraquinones and terpenoids were present in little quantities. On the other hand however, cardiac glycosides were absent in the plant. In the FRAP assay method, the absorbance of Vernonia amygdalina was found to be dose dependent with the maximum absorbance of 0.641nm at 0.5mg/ml which was significantly higher than that of rutin (0.56nm) and lower than that of Vitamin E (0.77nm). The ABTS radical scavenging activity of Vernonia amygdalina showed a dose dependent increase in the inhibition of the ABTS radical scavenging activity (91.93, 95.42, 99.24, 99.34 and 99.53% at 0.025, 0.05, 0.1, 0.2 and 0.5mg/ml respectively). This was comparable to that of rutin. The extract and the reference antioxidant (Rutin and Vitamin E) promoted an inhibition of DPPH radical at all concentrations tested in this study. Vernonia amygdalina showed a relatively stable effect in inhibiting the DPPH radical at all doses tested reaching 74.76%, 69.11% and 86.90% for Vernonia amygdalina, Vitamin E and Rutin respectively at the highest concentration. Vernonia amygdalina showed a dose dependent increase in the inhibition of the nitric oxide radical. The major compounds obtained from the GC-MS analysis of the essential of Vernonia amygdalina in this study were caryophyllene oxide (23.48%), phytol (22.92%), 2-Pentadecanone, 6,10,14-trimethyl (12.98%), hexadecanoic acid ethyl ester (12.24%), Oxirane, heptadecyl (12.11%), benzaldehyde (4.97%), benzeneacetaldehyde (5.83%), and trans-beta-ionone (5.47%). The methanol leaf extract of Vernonia amygdalina inhibited the acetic acid induced writhing in a manner comparable with the standard drug used in this study. The paw licking (formalin) test produces a distinct biphasic response to pain stimulus and the extract caused a dose dependent decrease in the inhibition of pain in both phases of the formalin paw lick test.